Technology Acceptance model (TAM) untuk menganalisis penerimaan terhadap sistem informasi di perpustakaanM INFORMASI PERPUSTAKAAN - Fatmawati, Endang (IQRA: Jurnal Perpustakaan dan Informasi, 2015)
Technology acceptance can be defined as a userâs willingness to employ technology for the tasks it is designed to support. Technology Acceptance Model (TAM) introduced by Davis in 1986. TAM is considers user perceptions of ease of use and usefulness as the main factors affecting the acceptance level of any technology. TAMÂ  is model for explaining and predicting information system use in library. TAM model to determine the attitude of users towards a technology acceptance.Â  Â Keywords: library information system, TAM, ease of use, usefulness, user acceptance, technology acceptance.